Optimization of composite ring stiffened cylindrical hulls for unmanned underwater vehicles using multi-island genetic algorithm. (May 2018) - Song, Baowei; Lyu, Da; Jiang, Jun
The usage of composite material helps reducing structure's weight in many conditions. In this paper, The Composite Ring Stiffened Cylindrical Hulls used by Unmanned Underwater Vehicles is optimized in various depths. The optimization aims to reducing the weight of the composite ring stiffened cylindrical hulls. Two candidate composite materials, T700/Epoxy and B(4)5505/Epoxy, are chosen to form the outer shell and stiffeners. Number and shape of the stiffeners, ply angles, and the number of the plies are considered. The Multi-Island Genetic Algorithm (MIGA) is performed in MATLAB and a new two-step method is proposed in crossover operations. ANSYS parametric design language is integrated in optimization procedure to ensure the acceptance of the optimal result. The results reveal that the proposed two-step method for multi-island genetic algorithm is efficiency and robust in reducing the weight of the composite ring stiffened cylindrical hulls. The weight for optimized composite ring stiffened cylindrical hulls with T700/Epoxy shells and B(4)5505/Epoxy stiffeners is 10.5% lighter than that with single composite material when the operating depth is 200 m.